Effect of Fermentation towards Production of Phenolic Compounds from Syzygium campanulatum - Lim, Er Vin (2016)
Phenolic compounds are plant secondary metabolites that beneficial to the plant and to us human as well such as their anti-oxidant property. Searching and enhancing profile of phenolic compounds were always in action. Wastes such as garden leaf waste can be alternative source of phenolic compounds. Syzygium campanulatum is one of the planet in garden whereby pruning activities were done and the leaf waste was discarded. The aim of this study is to quantify the total phenolic content (TPC), total flavonoid content (TFC), anti-oxidant activity and total protein concentration of non-fermented, natural microbes and Aspergillus brasiliensis fermented Syzygium campanulatum leaf waste. Solid state fermentation at 25˚C and 37˚C were done on the leaf waste. Centrifugation and shaking incubation were done to extract the contents in the leaf waste. The percent yield of natural microbes and A. brasiliensis in production of the phytochemical contents that can be extracted from S. campanulatum leaf waste were calculated and compared. The highest mean absorbance of TPC was detected in extract of non-fermented leaf waste. The highest TFC and total protein were detected in natural fermented leaf waste using fermentation temperature of 25˚C. The highest anti-oxidant activity was detected in natural fermented leaf waste using fermentation temperature of 37˚C. This study showed that fermentations at both temperatures generally decreased the TPC and increased the TFC of S. campanulatun leaf waste. The percentage yield of TPC was -40.35% and -23.00% for natural fermentation and A. brasiliensis fermentation respectively at 25˚C and -49.03% and -26.71% respectively at 37˚C. The percentage yield of TFC was +36.81% and +7.40% for Natural fermentation and A. brasiliensis fermentation respectively at 25˚C and +13.09% and +11.20% respectively at 37˚C. Natural fermentation at 25˚C increased more TFC in S. campanulatum leaf waste.